The way that the pedagogical potential of ethno-cultural traditions of the peoples of the north influence the development of pupils' personality - Zhirkova, Zoya Semenovna; Kornilova, Alla Georgiyevna; Petrova, Tatiana Nikolaevna; Kornilov, Iurii Viacheslavovich; Unarova, Lyubov Dorofeevna (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
Event-based approach to ethno-cultural traditions could contribute to the formation of children's abilities to identify original meanings in the natural, spiritual, material environment of their lives. The aim of the study is to assess the impact of the pedagogical potential of ethno-cultural traditions of the peoples of the North on the development of students' personality. Research methods include questionnaire survey, observation, interview, expert evaluations, alongside with applying SPSS program. The survey included 37 schoolchildren of small Arctic schools, including nomadic schools of Tomponskiy herd. The article presents the processing and results of the questionnaire. Following the results of the study, we could state that we have substantiated the basic principles of the event approach of pedagogical practices and have indicated individually significant data to determine the impact of the pedagogical potential of ethno-cultural traditions of the Arctic peoples on the personality of students.